Search for exclusive Higgs and $Z$ boson decays to $φγ$ and $ργ$ with the ATLAS detector - ATLAS collaboration (2903 authors) (2018)
A search for the exclusive decays of the Higgs and $Z$ bosons to a $φ$ or $ρ$ meson and a photon is performed with a $pp$ collision data sample corresponding to an integrated luminosity of up to 35.6 $fb^{-1}$ collected at $\sqrt{s}=13$ TeV with the ATLAS detector at the CERN Large Hadron Collider. These decays have been suggested as a probe of the Higgs boson couplings to light quarks. No significant excess of events is observed above the background, as expected from the Standard Model. Upper limits at 95% confidence level were obtained on the branching fractions of the Higgs boson decays to $φγ$ and $ργ$ of $4.8×10^{-4}$ and $8.8×10^{-4}$, respectively. The corresponding 95% confidence level upper limits for the $Z$ boson decays are $0.9×10^{-6}$ and $25×10^{-6}$ for $φγ$ and $ργ$, respectively.